Analysis of the physical and mechanical properties of coal-based solid waste filling material at early ages - Wu, Zheng; Xu, Lizhen; Xin, Chang; Zhang, Wen (Frontiers in Materials, 2025)
Fly ash-based filling materials are widely used in coal mine backfilling due to their cost-effectiveness and environmental benefits, but their application is often hindered by low early-age strength, poor fluidity, and severe water segregation. This study aims to enhance the performance of such materials by examining the effects of varying water-to-binder ratios and fly ash contents on their early-age physical and mechanical properties. Five different mix proportions composed of cement, fly ash, and coal gangue were prepared and tested. Uniaxial compressive strength, elastic modulus, and porosity were measured over a 12–48 h curing period, and hydration characteristics were analyzed using XRD and SEM techniques. Results show that reducing fly ash content from 75% to 50% increases the 48-h uniaxial compressive strength and elastic modulus by 3.06 and 6.80 times, respectively, due to improved hydration kinetics and microstructural compactness. Furthermore, incorporating early-strength additives further enhances mechanical performance. These findings suggest that a mix with 50% fly ash and a water-to-binder ratio of 0.63 achieves optimal early-age strength and compactness, providing a practical solution for improving the performance and applicability of coal-based solid waste filling materials in mine backfilling operations.